2016
DOI: 10.1021/acs.energyfuels.6b01870
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Combustion of Low Calorific Oil Shale Semicoke in Fluidized Bed System

Abstract: Oil shale semicoke produced from the oil shale retorting process causes great hazards to the environment due to its high phenol and polycyclic aromatic hydrocarbons content. A good solution of the current of semicoke is to burn it as feedstock. In the present work, the extremely low calorific oil shale semicoke of 2384 kJ/kg was adopted, and a series of experimental investigations and computational analyses were carried out in bench-scale and pilot-scale bubbling fluidized bed combustors, to understand its com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…This implied negative interactions between SC and FR and an undesirable course of the co-pyrolysis process. This might be explained by the presence of minerals such as SiO 2 , Al 2 O 3 , Fe 2 O 3 and CaO in SC [14]. Previously it has been demonstrated that the active acid sites in Al 2 O 3 could catalyze the decomposition of biomass [8].…”
Section: Synergy Between Blended Samplesmentioning
confidence: 99%
“…This implied negative interactions between SC and FR and an undesirable course of the co-pyrolysis process. This might be explained by the presence of minerals such as SiO 2 , Al 2 O 3 , Fe 2 O 3 and CaO in SC [14]. Previously it has been demonstrated that the active acid sites in Al 2 O 3 could catalyze the decomposition of biomass [8].…”
Section: Synergy Between Blended Samplesmentioning
confidence: 99%
“…Oil shale, a kind of unconventional petroleum resource with massive reserves, has attracted more attention in the last few years due to the contradiction between the increasing global energy consumption and shortage of conventional nonrenewable fossil fuels, such as crude oil, coal, and natural gas, 1 which is 10 times more than the liquid petroleum reserves, making it a great potential to become an alternative for conventional fossil energy. 2 The kerogen, contained with a proportionally large amount in oil shale, can be converted into hydrocarbons by thermal degradation, which is the prevalent method of oil shale utilization. 3,4 However, the thermal decomposition of oil shale requires high energy input, such as heating crude oil shale to 550 °C with 700 °C hot carrier gas, which is the most challenging obstacle to oil shale pyrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Oil shale, a kind of unconventional petroleum resource with massive reserves, has attracted more attention in the last few years due to the contradiction between the increasing global energy consumption and shortage of conventional nonrenewable fossil fuels, such as crude oil, coal, and natural gas, which is 10 times more than the liquid petroleum reserves, making it a great potential to become an alternative for conventional fossil energy …”
Section: Introductionmentioning
confidence: 99%